Comparative Dynamic Transcriptome Reveals the Delayed Secondary-Cell-Wall Thickening Results in Altered Lint Percentage and Fiber Elongation in a Chromosomal Segment Substitution Line of Cotton (Gossypium hirsutum L.) - Gao, Yang; Chen, Yu; Song, Zhangqiang; Zhang, Jingxia; Lv, Wanyu; Zhao, Han; Huo, Xuehan; Zheng, Ling; Wang, Furong; Zhang, Jun; Zhang, Tianzhen (Frontiers in Plant Science, 2021)
Lint percentage (LP) is an important yield component in cotton that is usually affected by initial fiber number and cell wall thickness. To explore how fiber cell wall development affects LP, phenotypic identification and dynamic transcriptome analysis were conducted using a single segment substitution line of chromosome 15 (SL15) that harbors a major quantitative trait locus (QTL) for LP. Compared to its recurrent parent LMY22, SL15 did not differ in initial fiber number, but the fiber cell wall thickness and single-fiber weight decreased significantly, altering LP. The comparative transcriptome profiles revealed that the secondary cell wall (SCW) development phase of SL15 was relatively delayed. Meanwhile, the expression of genes related to cell expansion decreased more slightly in SL15 with fiber development, resulting in relatively higher expression at SL15_25D than at LMY22_25D. SCW development-related genes, such as GhNACs and GhMYBs, in the putative NAC-MYB-CESA network differentially expressed at SL15_25D, along with the lower expression of CESA6, CSLC12, and CSLA2. The substituted chromosomal interval was further investigated, and found 6 of 146 candidate genes were differentially expressed in all four cell development periods including 10, 15, 20 and 25 DPA. Genetic variation and co-expression analysis showed that GH_D01G0052, GH_D01G0099, GH_D01G0100, and GH_D01G0140 may be important candidate genes associated with qLP-C15-1. Our results provide novel insights into cell wall development and its relationship with LP, which is beneficial for lint yield and fiber quality improvement.